2015
DOI: 10.1016/j.ymeth.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

oxBS-450K: A method for analysing hydroxymethylation using 450K BeadChips

Abstract: HighlightsA method is presented for 5hmC detection and analysis using Infinium 450K BeadChips.The oxBS-450K method can discriminate between 5mC and 5hmC in human gDNA5hmC levels were quantified genome-wide in 3 distinct biological samples.The reported 5hmC signal was validated using mass spectrometry and pyrosequencing.The effects of differing amounts of input DNA on final 5hmC call rate are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 19 publications
(26 reference statements)
10
74
0
Order By: Relevance
“…The application of the oxBS and BS protocol for 450 K arrays represents an opportunity to strike a balance between genomic resolution of 5 hmC and sample throughput. Importantly, the use of paired oxBS and BS 450 K arrays has consistently been shown to distinguish 5 hmC from both 5 mC and 5 C (refs 19, 20, 47). …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The application of the oxBS and BS protocol for 450 K arrays represents an opportunity to strike a balance between genomic resolution of 5 hmC and sample throughput. Importantly, the use of paired oxBS and BS 450 K arrays has consistently been shown to distinguish 5 hmC from both 5 mC and 5 C (refs 19, 20, 47). …”
Section: Discussionmentioning
confidence: 96%
“…Oxidation of 5 hmC to 5-formylcytosine (5 fC) is achievable with potassium perruthenate treatment, and subsequent sodium BS treatment (oxBS) converts 5 fC and cytosine to uracil and ultimately thymine while only 5 mC remains unconverted by the coupled oxBS treatment18. As a result, the selective oxidation step enables disambiguation of 5 hmC from 5 mC measurements1920. Recently, it has been demonstrated that use of paired BS and oxBS treatment on the same samples followed by hybridization to the Infinium DNA methylation array reliably permits accurate quantification of 5 hmC and 5 mC1920.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A growing appreciation for the role of 5hmC in biological processes and disease prompted the addition of an oxidation step prior to BS treatment (oxBS) that selectively oxidizes 5hmC to resolve 'true' 5mC levels. Paired BS and oxBS treatment on the same samples followed by hybridization to the Illumina 450K array now permits the differentiation of 5hmC from 5mC (Field et al, 2015;Stewart et al, 2015). However, naïve estimation of 5hmC via the difference in values between oxBS and BS signals …”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Morris et al provide an overview and introduction to available analysis pipelines and packages, as well as some selected applications of the array [3]. One of these is utilizing the array to measure hydroxymethyl-cytosine (hmC), which is described in more detail in the contribution by Stewart et al [4]. Methyl-cytosine (mC) can be oxidized by the family of Ten-eleven translocation (Tet) enzymes to hmC and, further, to formylcytosine (fC) and carboxycytosine (caC) [5,6].…”
mentioning
confidence: 99%